Estresse oxidativo mediado por extrato aquoso de Bauhinia forficata L. durante a fase de germinação e desenvolvimento de Phaseolus vulgaris L. - Porto, Erly Carlos (2018)
Plant species can interact with each other through the production and release of chemical compounds released into the environment, such an event is known as allelopathy. The objective of the present study was to investigate the allelopathic action and oxidative stress of the aqueous extract of Bauhinia forficata L. on seeds during the germination process and seedlings during the Phaseolus vulgaris development phase. The germination behavior, allelopathic activity index, initial growth and activity of antioxidant enzymes were studied at different times of seed imbibition, in the cotyledon (reserve tissue) and in the embryonic axis and seedlings, for aerial part and root target species. The results indicated that during the germination phase there was negative interference of B. forficata extracts on the seeds for germination, speed index and mean germination time, as well as the allelopathic activity index. In relation to the enzymatic activity, a high enzyme activity was observed at the beginning of seed imbibition, between 3 and 6 hours for the cotyledon and high activity in the embryonic axis at the end of the germination process, between 12 and 24 hours of imbibition. The increase of the extract proportions of the leaves of B. forficata affected the enzymatic activities in the germination process of the bean seeds, resulting in a delay of the germination. As for the development phase, there was reduction of the average length and dry mass of the root as the proportion of extract used increased. the levels of lipid peroxidation for both shoot and root were high, as well as the activity of the catalase enzyme for the roots was also elevated when submitted to the treatments with the presence of the extract. Thus, the increase in the proportion of B. forficata extract negatively affected the initial development, being the primary root elongation more sensitive, causing severe damage to the membranes of the bean seedlings roots.